Where we are and where we ought to be: The need for research-based assessments for dual language immersion learners. (3rd April 2022) - Thane, Patrick; Goldin, Michele; Jimenez, Abril; Hur, Esther; Lopez Otero, Julio Cesar; Austin, Jennifer
ABSTRACT: In this paper, we address a lack of assessments of partner language development in dual language immersion (DLI) programs. We propose several important considerations that are necessary for the creation of research-based assessments of partner language development in DLI programs, focusing on Spanish as an example. We first discuss what these assessments need to test, concentrating on different areas of language that have proven to be challenging for heritage speakers and second language learners of Spanish, both of whom are students in these immersion programs. Next, we discuss how to assess these students through the use of implicit and explicit tasks and by measuring production and comprehension separately. We also advocate for embracing students' translanguaging practices. Finally, we discuss why we need to assess partner language development. We propose that designing assessments that are simple to interpret will allow teachers, linguists, and policymakers to benefit from the data that they provide. For example, assessments of partner language development can contribute to assessment literacy and the creation of learning standards for bilingual schools. We argue that these considerations are essential for bringing DLI education to where we ought to be in the 21st century.